Epidemiological Study of an Acinetobacter baumannii Outbreak by Using a Combination of Antibiotyping and Ribotyping - Biendo, M. (American Society for Microbiology, 1999)
From June to November 1994 (period 1) and from February to June 1995 (period 2), multiresistant Acinetobacter baumannii strains were isolated in intensive care units and surgical wards of the Amiens Teaching Hospital Center (Amiens, France). Eighteen isolates were obtained from 17 (1%) of 1,706 patients admitted during both of these periods, giving an incidence rate of nosocomial infection per 1,000 patient days of 0.6%. Of 17 infected patients, 9 had pneumonia, 3 had urinary tract infection, 2 had peritonitis, 1 had septicemia, 1 had a catheter infection, and 1 had pneumonia and urinary tract infection. According to typing results, four antibiotic resistance profiles were detected: a, b, c, and d; seven ribotypes were distinguished by both restriction enzymes EcoRI and SalI (A, B, C, D, E, F, and G). By combining antibiotyping and ribotyping, we obtained eight groups of strains (groups I to VIII). Group I contained five strains (strains 4, 5, 7, 8, and 9) which had antibiogram pattern a and ribopattern A and constituted the outbreak strains. The strains of group II (strains 3, 10, 11, 13, and 14) were closely related to outbreak strain A and appeared to be variants of ribotype A (A2 [strain 3]; A4 [strain 10]; A5 [strains 11, 13, and 14]). Groups III, IV, V, VI, VII, and VIII included strains which were epidemiologically unrelated to the strains of group I and were considered nonoutbreak strains.